"It's Not Really My Job": A Mixed Methods Framework for Language Ideologies, Monolingualism, and Teaching Emergent Bilingual Learners. (March 2020) - Bacon, Chris K.
Teacher education has redoubled efforts to prepare a predominantly monolingual teaching force for linguistic diversity in U.S. schools. Some jurisdictions are requiring specific teacher preparation, such as mandated Sheltered English Immersion (SEI) endorsement in Massachusetts, the context of this study. Previous research has explored the intersections of language ideologies and practice through such coursework. However, few studies have accounted for the underlying monolingual ideologies that inform U.S education. Therefore, this study employs a mixed methods approach to analyze language ideologies among 127 preservice and beginning teachers engaged in SEI methods coursework. Drawing on written reflections, survey data, and reported practices, this study offers a framework for exploring teacher language ideologies. This framework highlights a trajectory of lived ontologies, pedagogical orientations, and key contextual "filters" that may distort language ideologies in practice. The framework is operationalized through an analysis of monolingual ideologies across educational policy, practice, and teacher preparation.